Feeding Behaviors Of Sandelwood Pony (Equus caballus) Adult Male Contained in Kambuhapang Village, Lewa Subdistrict Sumba Timur District - Dima, Alfred O. M.; Nazer, Burhanudin; Ati, Vinsen M.; Meye, Ermelinda D.; F. M, Ike Septa; Amalo, Djeffry (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2021)
The objective of this study was to determine feeding behavior include the frequency prehention, mastication, and defecation of Sandelwood pony. The study used five of local Sandelwood pony males with an agerange of Â±4 years old and initial weight were 240-260 kg. The were fed randomly with for agemixed with concentrate in 3 periods feeding. Thus, adlibitum animal sampling method was used for this study. Data behaviors and frequency of prehention, mastication, and defecation was analyzed using analysis of drescriptive statistics. There sults showed that prehention behaviors sequentially include the horse walking to ward the feed, leng the ning the neck, taking the feed using the upperlip and teeth to cut feed with the highest frequency at the time of morning day. Mastication behaviors was characterized by movement of the upper and lower jaw to reduce feed particles with frequency morning day highest compared to the other feeding administrations. Mastication behaviors sequence in volves kissing the site of the old dirt and then lifting his tail and removing the stool thrpuough the anus. Finally, they kissed again where the stool threw away and left the place. Morphologically, faeces namely oval, round and irregular with abrownish green color.